Konsep Manusia Sebagai An-Nas dalam Al-Qur’an - Magfiroh, Norma Hasanatul; Soleh, Achmad Khudori (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2025)
Humans, who are actually the most perfect created creatures, apparently have such complex meanings. Humans tend to be interpreted as social, psychological and biological creatures or even a combination of these things. The aim of this article is to study and explore the concept of humans as An-Nas in the Al-Qur'an. This research uses the literature review method with various sources and analysis used and the Maudhu'i interpretation method by interpreting the Al-Qur'an by collecting several verses that have the same theme and then interpreting them in detail. The writing results show (1) Lafadz An-Nas is mentioned in the Qur'an 251 times which is spread in 86 forms with the same writing model, namely An-Nas. (2) The context of the meaning of the lafadz An-Nas in the Qur'an is generally divided into three, namely showing social groups with their distinctive characteristics, some humans have low qualities, and humans are meant socially, not just individuals. (3) The concept of An-Nas in social society is described as being that humans are creatures that have many dimensions, so they should help each other, respect and help each other, especially in the Unitary State of the Republic of Indonesia.